ONOMATOPOEIA IN THE ENGLISH LANGUAGE: ONOMATOPOEIA IN THE ENGLISH LANGUAGE - Abdiganieva, Dilnaz (Журнал иностранных языков и лингвистики, 2025)
In English, auditory sensations are used in comparison with visual sensations. Sound is the signal of one or another event in reality. It should be noted that sound perception is easier than, for example, color perception. Because we usually conclude by observing the color of an object over a long or short period of time, and often we don't limit the time in this period. We receive the sound quickly in a relatively short time. Imitative words are divided into several types depending on the process of word addition in imitation of identified objects and sounds.